Depinning of bubble contact line on a biphilic surface in subatmospheric boiling: Revisiting the theories of bubble departure. (November 2018) - Shen, Biao; Yamada, Masayuki; Mine, Tomosuke; Hidaka, Sumitomo; Kohno, Masamichi; Takahashi, Koji; Takata, Yasuyuki
Highlights: Visualization is performed of bubble growth on a biphilic surface under low pressures. Bubble departure diameter shows a mechanistic transition with decreasing pressures. A simple predictive model demarcating the bubble contact line mobility is derived. Abstract: Boiling suffers from inefficient intermittent cycles of bubble generation under subatmospheric conditions. Such deterioration in heat transfer rates can be alleviated but not completely eliminated by use of mixed-wettability (biphilic) surfaces. Here we study bubble dynamics on a single hydrophobic spot in low-pressure pool boiling. The results reveal an interesting transition in bubble departure behavior from the surface-driven mode to the drag-driven mode, which correlates closely with the dynamic state of the three-phase contact line on the surface. Based on the force-balance argument, a simple model is derived to map the contact-line mobility during bubble growth. It is found that below a certain threshold pressure, the bubble base expansion is increasingly likely to overcome the strong pinning of the contact line at the interface between the hydrophobic and hydrophilic regions. That could lead to total removal of vapor residues from the surface and cause deactivation of the nucleation site, which portends the eventual takeover of intermittent boiling on the biphilic surface.